Design of Innovative Biocompatible Cellulose Nanostructures for the Delivery and Sustained Release of Curcumin - Casanova, Francisca; Pereira, Carla F.; Ribeiro, Alessandra B.; Costa, Eduardo M.; Freixo, Ricardo; Castro, Pedro M.; Fernandes, João C.; Pintado, Manuela; Ramos, Óscar L. (Pharmaceutics, 2023)
Poor aqueous solubility, stability and bioavailability of interesting bioactive compounds is a challenge in the development of bioactive formulations. Cellulose nanostructures are promising and sustainable carriers with unique features that may be used in enabling delivery strategies. In this work, cellulose nanocrystals (CNC) and cellulose nanofibers were investigated as carriers for the delivery of curcumin, a model liposoluble compound. Nanocellulose modification with the surfactant cetyltrimethylammonium bromide (CTAB), tannic acid and decylamine (TADA), and by TEMPO-mediated oxidation were also tested and compared. The carrier materials were characterized in terms of structural properties and surface charge, while the delivery systems were evaluated for their encapsulation and release properties. The release profile was assessed in conditions that mimic the gastric and intestinal fluids, and cytotoxicity studies were performed in intestinal cells to confirm safe application. Modification with CTAB and TADA resulted in high curcumin encapsulation efficiencies of 90 and 99%, respectively. While no curcumin was released from TADA-modified nanocellulose in simulated gastrointestinal conditions, CNC-CTAB allowed for a curcumin-sustained release of ca. 50% over 8 h. Furthermore, the CNC-CTAB delivery system showed no cytotoxic effects on Caco-2 intestinal cells up to 0.125 g/L, meaning that up to this concentration the system is safe to use. Overall, the use of the delivery systems allowed for the reduction in the cytotoxicity associated with higher curcumin concentrations, highlighting the potential of nanocellulose encapsulation systems.